Haplocauda, a New Genus of Fireflies Endemic to the Amazon Rainforest (Coleoptera: Lampyridae) - Silveira, Luiz Felipe Lima da; Lima, William; Fonseca, Claudio Ruy Vasconcelos da; McHugh, Joseph V. (Insects, 2022)
Most firefly genera have poorly defined taxonomic boundaries, especially in the Neotropics, where they are more diverse and more difficult to identify. Recent advances that shed light on the diversity of fireflies in South America have focused mainly on Atlantic Rainforest taxa, whereas lampyrids in other biomes remained largely unstudied. We found three new firefly species endemic to the Amazon basin that share unique traits of the male abdomen where sternum VIII and the pygidium are modified and likely work as a copulation clamp. Here we test and confirm the hypothesis that these three species form a monophyletic lineage and propose Haplocauda gen. nov. to accommodate the three new species. Both maximum parsimony and probabilistic (Bayesian and maximum likelihood) phylogenetic analyses confirmed Haplocauda gen. nov. monophyly, and consistently recovered it as the sister group to Scissicauda, fireflies endemic to the Atlantic Rainforest that also feature a copulation clamp on abdominal segment VIII, although with a different configuration. We provide illustrations, diagnostic descriptions, and keys to species based on males and females. The three new species were sampled from different regions, and are likely allopatric, a common pattern among Amazonian taxa.
Keywords: Fireflies; Photinus Pyralis; Bioluminescence